FABP3 Deficiency Exacerbates Metabolic Derangement in Cardiac Hypertrophy and Heart Failure via PPARα Pathway - Zhuang, Lingfang; Mao, Ye; Liu, Zizhu; Li, Chenni; Jin, Qi; Lu, Lin; Tao, Rong; Yan, Xiaoxiang; Chen, Kang (Frontiers in Cardiovascular Medicine, 2021)
Background: Cardiac hypertrophy was accompanied by various cardiovascular diseases (CVDs), due to the high global incidence and mortality of CVDs, it has become increasingly critical to characterize the pathogenesis of cardiac hypertrophy. We aimed to determine the metabolic roles of fatty acid binding protein 3 (FABP3), on transverse aortic constriction (TAC)-induced cardiac hypertrophy. Methods and Results: TAC or Ang II treatment markedly upregulated Fabp3 expression. Notably, Fabp3 ablation aggravated TAC-induced cardiac hypertrophy and cardiac dysfunction. Multi-omics analysis revealed that Fabp3-deficient hearts exhibited disrupted metabolic signatures characterized by increased glycolysis, toxic lipid accumulation, and compromised fatty acid oxidation and ATP production under hypertrophic stimuli. Mechanistically, FABP3 mediated metabolic reprogramming by directly interacting with PPARα, which prevented its degradation and synergistically modulated its transcriptional activity on Mlycd, Gck. Finally, treatment with the PPARα agonist, fenofibrate, rescued the pro-hypertrophic effects of Fabp3 deficiency. Conclusions: Collectively, these findings reveal the indispensable roles of FABP3-PPARα axis on metabolic homeostasis and the development of hypertrophy, which sheds new light on the treatment of hypertrophy.